A flow-network approach for equilibrium of material requirements planning - Yenisey, Mehmet Mutlu (Elsevier BV, 2006)
Abstract Material requirements planning (MRP) has been a very popular and widely used multi-level inventory control method since 1970s. Recent developments in computer and information technology accelerate and facilitate the calculations necessary for MRP, but MRP is simply a system to open and trace the production/purchasing orders under pre-determined lead-time and lot size constraints. It does not directly include any optimization feature. In this article, an approach, which consists of the Flow Network with Side Constraints, is discussed in order to optimize the material flows in MRP problems. Additionally, an example case is given in order to show the applicability of the flow network formulation to APS. The model of the example case is solved and the computational results are given.